Case Report: Complex cardiac arrhythmia management in the ICU for an adolescent with Friedreich ataxia - Fashina, Oluwatomini A.; Gleich, Stephen J.; Opp, Derek N.; Ouellette, Yves; Kawai, Yu (Frontiers in Pediatrics, 2025)
BackgroundFriedreich ataxia (FRDA) is a progressive neurodegenerative disorder with specific clinical manifestations, such as scoliosis, which may impact the management of cardiac arrhythmias and heart failure.Case descriptionA 17-year-old male with FRDA and hypertrophic cardiomyopathy presented with atrial flutter and resultant acute-on-chronic systolic and diastolic heart failure with reduced ejection fraction. The arrhythmias were refractory to medical management with adenosine and amiodarone. An attempted cavotricuspid isthmus ablation was unsuccessful due to abnormal cardiac positioning caused by severe scoliosis. Despite optimization with dofetilide and metoprolol, he was readmitted with recurrent atrial arrhythmias and cardiogenic shock, secondary to probable amiodarone-induced thyrotoxicosis, requiring extracorporeal membrane oxygenation. His clinical course involved multisystem complications, prolonged hospitalization, and disease progression, with no recovery in systolic function despite control of his arrhythmia burden.ConclusionIntensivists should be cognizant of multisystem complications that can arise when treating refractory cardiac arrhythmias, especially in those with concomitant genetic conditions.